Evaluation of Si Kesi Gemes implementation (strengthening system of Kelurahan Siaga in the framework of healthy living community movement) in the City of Yogyakarta - Ulfah, Meirina; Supriyati; Nurhadi (BKM Public Health and Community Medicine, 2023)
Purpose: Kelurahan siaga is a form of community empowerment. The latest data from Pusdatin in 2013 shows that the percentage amount of desa and kelurahan siaga aktif in Indonesia was 65.2%, and in DIY was 94.3%. The percentage of kelurahan siaga in Yogyakarta City in 2016 reached 100% but experienced torpidity. The kelurahan siaga was revitalized by establishing the Si Kesi Gemes network. This study aimed to evaluate the implementation of Si Kesi Gemes in Yogyakarta City. Methods: This research used a qualitative descriptive exploratory study with a single case study design. The selection of informants was carried out by purposive sampling. The selected informants were local officials and non-governmental organizations registered in the Si Kesi Gemes network. Data were collected using Focussed Group Discussion (FGD), in-depth interviews and observations. FGDs were conducted in 2 groups by undertaking in-depth interviews with 21 participants. The data validity was done using triangulation and peer debriefing. Results: The formation of Si KesiGemes was done using a combination of top-down and participatory approaches. The top-down approach means that the network is initiated and formed by the Health Office, while the participatory approach means that Kesi is involved in the regional network formation. Si Kesi Gemes plays a role in activating the coordination of Kesi and extending cooperation with private health service facilities, health colleges, and local employers. The effectiveness of Si Kesi Gemes is indicated through the accommodation of Kesi in the village fund, the liveliness of the village coordination forums, the funding from CSR, the activeness of UKBM Posbindu, and the presence of innovative activities. Public health centers still dominate UKBM coaching, and the training does not meet the needs of participants. Conclusion: The formation of Si Kesi Gemes is indispensable for binding the involvement of the networks in supporting Kelurahan Siaga. Kesi, FKKS, and FKS are expected to schedule regular coordination at the village, sub-district, and city levels.